Design and Build a Website-Based Word Template Automation System Using the Prototype Method - Haliza, Sitti Nur; Ainnur, Abdull; Effendi, Ilham Julian (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
In administrative and banking environments, the use of Word templates that must be adapted to specific data before use is often necessary. The manual process of replacing data in these templates requires significant time and effort. Therefore, this research aims to design and implement an automation system that allows for the automatic replacement of data in Word templates. The method used in this research is the prototype method, enabling developers to create system prototypes that can be tested by users before further development is carried out. In the design stage, frequently used Word templates in business and administrative environments are identified and categorized. An efficient and accurate data replacement algorithm is then designed and implemented using a suitable programming language. The resulting automation system is designed in the form of a website, allowing users to input data to be filled into the template. Users can also preview the input data before downloading the customized Word file. The results of this research are expected to reduce the time and effort required to replace data in Word templates manually. The implemented automation system in the form of a website provides flexibility and ease of use for users who want to replace data in their Word templates. The prototype method allows for iteration and adjustment of the system based on user feedback, thereby increasing satisfaction and effectiveness in system use.